Europas musikhistoria: Verklighet eller etnocentrisk fiktion? - Ling, Jan (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1985)
Europe as a conceptual unit in Music History How should music history be presented today so that we can understand contemporary music. the music which has been preserved from the past. music in society today and in the past'? In order to answer these questions in connection with writing a second volume of a Music History of Europe. a selection of different traditions in music history writing are presented. from the end of the 17th century to today. Various approaches of the narrative traditions of style, culture. biography are looked upon as tools used in various ways and for various general ideological aims. The dialectic interplay among various types of music is found to be an ongoing worldwide phenomenon: in this context Europe is one extremely interesting area of study. with a wealth of traditions and continual influence from near and far. The ordinary music histories. geographically limited to Western Europe and concentrated on ars musica and its present-day offshots, are to be completed with works that emphasize all that unites Western and Eastern Europe in art and folk music. The "heroes" of music in Vienna or Berlin must be seen in the light of music styles emerging in the "Randgebiet" of Europe and as branches of a common European music tree. In the last pages the Content of Part II of the European Music history is presented.